2020
DOI: 10.1039/d0cc00233j
|View full text |Cite
|
Sign up to set email alerts
|

An endoplasmic reticulum-targeting fluorescent probe for imaging ˙OH in living cells

Abstract: A new ER-targeting fluorescent probe for ˙OH is developed and applied to imaging ˙OH generation as well as lipid droplet formation in ER stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…9), for imaging • OH in living cells. 85 In the absence of • OH, the probe itself exhibited stable fluorescence at 446 nm, whereas when • OH was added, the emission at 446 nm increased immediately and continuously. This probe was highly selective to • OH and was stable in different pH buffer and solvents.…”
Section: Er-targetable Fluorescent Probesmentioning
confidence: 97%
“…9), for imaging • OH in living cells. 85 In the absence of • OH, the probe itself exhibited stable fluorescence at 446 nm, whereas when • OH was added, the emission at 446 nm increased immediately and continuously. This probe was highly selective to • OH and was stable in different pH buffer and solvents.…”
Section: Er-targetable Fluorescent Probesmentioning
confidence: 97%
“…Observation with fluorescent reagents (e.g., dihydrorhodamine, coumarin-3-calboxylic acid, and endoplasmic reticulum (ER)-targeting OH • probe) has revealed intracellular localization of the generated OH • . Such studies have reported that ER by the Fenton reaction [ 53 , 54 ] regulates hypoxia-inducible gene expression. ER stress has been reported to regulate more than one-third of all proteins made in the cell in synthesis, folding, and structural maturation [ 55 ].…”
Section: Fenton Reaction In Bodymentioning
confidence: 99%
“…As an important organelle in cells, endoplasmic reticulum plays a key role in cell metabolism, protein synthesis and transmission of intermediates and signal molecules (Zhang M.-M. et al, 2020;Zhao et al, 2020). Tang's group reported an AIE material 9 based on cyanostillbene skeleton by simple functionalization ( Figure 3A) (Alam et al, 2020).…”
Section: In Vitro Cell Imagingmentioning
confidence: 99%